(untitled) (American Journal of Business Management, Economics and Banking, 2024)
Convergence technologies such as blockchain, artificial intelligence (AI), digital payments, crowdfunding, and peer-to-peer (P2P) lending are transforming the global financial sector. These innovations accelerate trade finance, reduce risks, and promote financial inclusion by offering new tools for import–export operations. This paper examines the role of these technologies in global trade finance, highlights international experiences from the United States, China, the United Kingdom, and Japan, and analyzes Uzbekistan’s position. The study also explores the challenges Uzbekistan faces in adopting such innovations, including limited access to export credit insurance, underdeveloped FinTech infrastructure, and currency risks. Using recent global data and trade figures, policy recommendations are proposed to enhance Uzbekistan’s competitiveness in the international market.